The discursive constitution of the \'management control\' organisation - Barroso, Marcelo Francini Girão (2014)
The idea of \'management control\' regards stability within the organisational environment, in the sense of directing the behaviour of employees towards some set of \'organisational\' objectives. More than a collection of managerial artefacts, however, this signifier labels a specific set of objects and practices, which typify a regime of practices \'management control\' at the same time that they are driven, enabled and constrained by it. In this sense, diverse \'organisation\'-like social and political logics are materialised through these objects and practices and through the crystallised regime of practices, then being recognised as \'management control\'-like constitutive logics. Throughout the exercise of such logics - political institutions of social logics - a \'management control\'-like organisational discourse is constituted, hence constituting the \'management control\'-like \'organisation\', then being experienced as a typical \'management control\' organisation. The organisation - and the \'management control\'-like organisation - does not happen as a random phenomenon, but it happens out of the constitution of \'management control\'-like organisational discourse. The present thesis develops the arguments towards this essential description, working on post-structuralist discourse theory and following a retroductive circle of problematisation, theory construction and persuasion/intervention for research in social sciences, willing to answer the research question regarding the dynamic whereby \'management control\' logics are articulated and thus constitute contextually-specific organisational discourses. A case study has been developed at the Enterprise, a family-owned metallurgic business, and five theoretical contributions are then proposed, regarding the dynamic process of constituting the organisation, the conceptual difference between discourse theory and institutional theory, the powerful role of political actors for instituting, de-instituting and re-instituting social logics, the relevance of using management accounting artefacts as tools for materialising \'management control\' social logics, and the materialisation of \'management control\'-like hegemonic discourse through the feedforward process with the articulation of the regime of practices.